Fiscal Incidence in Belarus : A Commitment to Equity Analysis - Bornukova, Kateryna (World Bank, Washington, DC, 2017)
The paper employs the Commitment to Equity framework to present a first attempt at a comprehensive fiscal incidence analysis for Belarus, encompassing the revenue and expenditures components of the fiscal system, including direct and indirect taxes, as well as direct, indirect, and in-kind transfers. The analysis reveals that fiscal policies in Belarus effectively redistribute income from the top to the bottom of the income distribution. Direct transfers, especially pensions, are the most equalizing and pro-poor of the fiscal interventions—direct transfers and direct taxes lower the national poverty headcount by 17 percentage points and lower the Gini index of inequality from 0.407 to 0.267. Some of the indirect taxes, by contrast, are regressive and indirect transfers -- poorly targeted, such that the effect of these components of the fiscal system is not equalizing. Finally, the cost-efficiency of different parts of the fiscal system in Belarus varies considerably. Unemployment benefits, pensions, and child benefits are found to be cost -- efficient, while indirect subsidies are highly cost-inefficient. The analysis points toward possible reforms that would allow reducing poverty and inequality more efficiently.